2008
DOI: 10.1002/cpp.572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mental health continuum–short form (MHC–SF) in setswana‐speaking South Africans

Abstract: A continuous assessment and a categorical diagnosis of the presence of mental health, described as flourishing, and the absence of mental health, characterized as languishing, is applied to a random sample of 1050 Setswana-speaking adults in the Northwest province of South Africa. Factor analysis revealed that the mental health continuum-short form (MHC-SF) replicated the three-factor structure of emotional, psychological and social well-being found in US samples. The internal reliability of the overall MHC-SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

48
664
7
22

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 783 publications
(741 citation statements)
references
References 24 publications
48
664
7
22
Order By: Relevance
“…Examination of item content to devise labels for the factors led us to name the first factor "personal well-being" (PWB) and the second factor-comprised of those MHC-SF items that ask for the respondent's opinions about society, rather than personal introspection "evaluative perception of the social environment" (EPSE). Thus, our EFA findings show that, although it appears that the MHC-SF does seem to emulate a two-factor structure, the distribution of high item loadings across the factors does not conform to what Cole and Fredrickson (14) reported, nor to what other published studies have found (11,13).…”
Section: Theoretical and Methodological Issuescontrasting
confidence: 95%
See 3 more Smart Citations
“…Examination of item content to devise labels for the factors led us to name the first factor "personal well-being" (PWB) and the second factor-comprised of those MHC-SF items that ask for the respondent's opinions about society, rather than personal introspection "evaluative perception of the social environment" (EPSE). Thus, our EFA findings show that, although it appears that the MHC-SF does seem to emulate a two-factor structure, the distribution of high item loadings across the factors does not conform to what Cole and Fredrickson (14) reported, nor to what other published studies have found (11,13).…”
Section: Theoretical and Methodological Issuescontrasting
confidence: 95%
“…According to Keyes (12), the MHC-SF assesses three forms of well-being: emotional well-being (items SF1-SF3), social well-being (items SF4-SF8), and psychological well-being (items SF9-SF14). This 3D structure has been confirmed in empirical studies (11,13). In an Appendix describing the technical details of the scoring of the MHC-SF, Keyes (12) applied the word "hedonic" to the first factor and "eudaimonic" (or "positive functioning") to the second and third, and indicated that a person's "flourishing" status depends on how many items from each of these two groups are experienced with a minimum specific frequency.…”
Section: Theoretical and Methodological Issuesmentioning
confidence: 77%
See 2 more Smart Citations
“…Conversely, an individual can simultaneously experience symptoms of psychopathology and maintain positive functioning and psychological flourishing. This “two-continua model” has been validated in multiple populations (Keyes, 2006; Keyes, Eisenberg, Dhingra, Perry, & Dube, 2012; Keyes et al, 2008) and using different measurements and conceptualizations of mental health and illness (Compton, Smith, Cornish, & Qualls, 1996; Greenspoon & Saklofske, 2001; Headey, Kelley, & Wearing, 1993; Suldo & Shaffer, 2008; Westerhof & Keyes, 2010). An important implication is that an individual is only completely healthy when he or she experiences both low levels of psychopathological symptoms and a good state of well-being.…”
Section: Introductionmentioning
confidence: 99%